Unrecognized HIV infection in asymptomatic volunteer blood donors at district Peshawar, Khyber Pakhtunkhwa, Pakistan. (May 2020) - Haq, I.; Ullah, R.; Din, M.; Ahmad, S.; Anwar, F.; Ali, M.; Khan, H. Ullah
Abstract: Acquired immunodeficiency syndrome (AIDS) is a global epidemic that impacts the lives of many individuals each year. Human immunodeficiency virus (HIV) is a retrovirus that infects human CD4 + T helper cells and macrophages thereby causing severe immune disease. The current study aimed to examine the prevalence of HIV among the blood donors of Khyber Pakhtunkhwa at Peshawar. In this study, a total of 8634 volunteers who donated blood were carefully screened for HIV using ELISA and RT-PCR techniques. Among the volunteers ( n  = 8634), 63 were positive by both ELISA and RT-PCR; which shows a prevalence of 0.73%. Both diagnostic techniques exhibited similar results. All the positive individuals were informed immediately and advised to start treatment to control the progression of the infection. It was concluded that HIV is on the rise in Peshawar, and routine screening and preventive measures are immediately required to address the urgent situation of HIV infection.